2001
DOI: 10.1097/00002030-200109280-00016
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality associated with tuberculosis–HIV-1 co-infection in Durban, South Africa

Abstract: Tuberculosis and HIV-1 are emerging as significant contributors to maternal mortality in KwaZulu Natal. Any attempt to improve maternal health must also include careful screening and investigation for tuberculosis in high-risk pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 21 publications
3
82
1
2
Order By: Relevance
“…11,12 Between 2011 and 2013, there was no change in the antenatal HIV-prevalence. 13 Substandard diagnostic care and delayed and missed diagnoses have been reported as some of the contributing factors to maternal mortality in rural communities in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Between 2011 and 2013, there was no change in the antenatal HIV-prevalence. 13 Substandard diagnostic care and delayed and missed diagnoses have been reported as some of the contributing factors to maternal mortality in rural communities in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…2 The findings of a study in Durban revealed a 3-fold higher maternal mortality ratio (MMR) among HIV-infected women with TB (12 170/100 000 live births) compared with TB-infected HIVuninfected women (3 850/100 000 live births) in the absence of antiretroviral therapy (ART). 11 Of the women diagnosed with TB, 79% were co-infected with HIV. 11 Similarly high MMRs in TB/HIV-co-infected women have been observed in a number of studies in sub-Saharan Africa.…”
mentioning
confidence: 99%
“…Observed indirect causes of maternal death in our study (anemia, HIV, malaria) are diseases closely associated with poverty [18]- [20].…”
Section: Discussionmentioning
confidence: 66%